The Relationship between the Attitude Towards Socioscientific Issues and Views on COVID-19 and Vaccine - SALMAN, Muhammed; YILMAZ, Adem (Bilge Akademi, 2021)
With the pandemic, conspiracy theories about the COVID-19 began to spread rapidly in the virtual environment. It is not difficult for these conspiracy theories to replace scientific knowledge, particularly those with low scientific literacy. This study aimed to examine whether there is a relationship between university students' attitudes towards socioscientific issues (viz. their views on conspiracy theories) and their views on the COVID-19 process and vaccination. 1275 university students from different universities studying at various departments participated in the study. “The Attitude Scale towards Socioscientific Issues" developed by Topcu (2010) and the "COVID-19 process and Vaccination Questionnaire" developed by the researchers consisting of 20 questions were used as data collection tools in the study. In analysing the data obtained from the application, the continuous variables with two categories were analysed using the independent groups' t-test since the research data showed normal distribution and provided the preconditions. A one-way ANOVA test was used in the analysis of continuous variables with more than two categories. The chi-square test was used in the analysis of categorical variables, and a multinominal logistic regression was performed when examining the relationship between main variables and categorical variables. As a result of the analysis, it was observed that students with a high attitude towards socioscientific issues were more scientifically oriented to conspiracy theories, the existence of the COVID-19 and its origin, and their ideas about vaccination were more positive. In the post-pandemic period, a restructuring of science education in which socioscientific issues are concentrated upon to increase health literacy and scientific literacy arguably appears urgent.
Keywords: Alan Eğitimleri; Socioscientific issues; COVID-19 process and vaccination; scientific literacy; science education; Other Fields of Education; 4. Education; 3. Good health